Growth-maximizing public debt in Turkey: An empirical investigation - Bulus, Gokay Canberk (Economics and Business Review, 2020)
The aim of the paper is to empirically estimate the growth-maximizing debtto- GDP ratio in the case of Turkey. To calculate the growth-maximizing debt-to-GDP ratio FMOLS, DOLS, and CCR estimators are used for the period from 1960–2013. According to the empirical findings the growth-maximizing debt-to-GDP ratio varies between 34.3% and 38.7%. Based on a comparison of these ratios to current data (29.1% for 2018), Turkey has the capacity for additional borrowing to achieve a growthmaximizing debt-to-GDP ratio. If this additional borrowing capacity is used for public investment with a return greater than the interest cost of the additional debt economic growth will be maximized and public debt sustainability supported.